Perception of Students about Homework in Mathematics - Bhatta, Balaram (Nepal Journal of Multidisciplinary Research, 2020)
Homework has been a source of debate in schools for the past several decades and will continue to be an important topic in the future. It is a traditional part of education but some debate its importance in the classroom. This study explored student perception of homework and their reported performance in basic and secondary level school mathematics. The research questions focused on student attitudes about homework, the relationship of students’ self-efficacy and support resources to their homework completion, and the relationship of students’ general level of achievement in mathematics with respect to gender, level and achievement level. The study involved a survey of 402 students of Tokha Municipality. The survey did not demonstrate reliable measurement of the hypothesized factors of purpose, self-efficacy, and support resources related to students’ overall perceptions about homework. However, overall, students reported positive attitudes and grades in math class. On the basis of gender and level in which students study, there is no significant difference on the perception while there is statistically significant difference on the basis of students' achievement in examination. It is recommended that a good and healthy home environment and sound teacher student relationship yields in good achievement score and boosts up overall perception on mathematics homework.